The costs of regime survival racial mobilization, elite domination, and control of the state in Guyana and Trinidad - Hintzen, Percy C. (The Arnold and Caroline Rose monograph series of the American Sociological Association, 1989)
This comparative study of two republics - Guyana in South America, and Trinidad and Tobago in the Caribbean - examines the conditions which determine regime survival in less developed countries. Given the structure of political and economic organization typical of these countries, and of the web of international relations of which they are a part, political survival can very often depend on a leader's willingness to serve the interests of a small, but politically strategic minority. In both Guyana and Trinidad post-independence leaders made politically expedient decisions that foreclosed policy choices consistent with the satisfaction of collective needs. As a result both countries experienced a series of political and economic crises. This in-depth comparative study of Guyana and Trinidad will be of interest to all scholars, students and policy-makers concerned with aspects of political and economic development in the Third World